Nitrous oxide production via enzymatic nitroxyl from the nitrifying archaeon Nitrosopumilus maritimus - Robert W. Voland; Hongsen Wang; Héctor D. Abruña; Kyle M. Lancaster (Proceedings of the National Academy of Sciences, 2025)
Ammonia oxidizing archaea (AOA) are among the most abundant microorganisms on earth and are known to be a major source of nitrous oxide (N 2 O) emissions, although biochemical origins of this N 2 O remain unknown. Enzymological details of AOA nitrogen metabolism are broadly unavailable. We report the recombinant expression, purification, and characterization of a multicopper oxidase, Nmar_1354, from the AOA Nitrosopumilus maritimus . We show that Nmar_1354 selectively produces nitroxyl (HNO) by coupling the oxidation of the obligate nitrification intermediate hydroxylamine (NH 2 OH) to dioxygen (O 2 ) reduction. This HNO undergoes several downstream reactions, although the major fates are production of N 2 via reaction with NH 2 OH and dimerization with itself to yield N 2 O. These results afford one plausible enzymatic origin for N 2 O release by AOA. Moreover, these results reveal a physiologically relevant enzymatic reaction for producing HNO, an enigmatic nitrogen oxide speculated to be operative in cellular signaling and in energy transduction.